1988
DOI: 10.1111/j.1464-410x.1988.tb04327.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Subcutaneous Heparin does not Increase Operative Blood Loss in Transurethral Resection of the Prostate

Abstract: A prospective randomised study of subcutaneous heparin compared with no heparin was performed in 60 patients undergoing transurethral resection of the prostate. Operative blood loss in the irrigation fluid was measured using a haemoglobinometer. Blood loss correlated with the amount of prostate resected and the duration of the procedure. Subcutaneous heparin had no significant effect on the measured blood loss in transurethral resection of the prostate and can be used as a safe means of prophylaxis against thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Most previous studies have also reported a significant positive relationship between the size of resection and operative blood loss (Abrams et al, 1982;Gentens et al, 1986;Wilson et al, 1988). More specifically, Fujita (1988) showed that this finding was not purely related to the increased resection time required.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most previous studies have also reported a significant positive relationship between the size of resection and operative blood loss (Abrams et al, 1982;Gentens et al, 1986;Wilson et al, 1988). More specifically, Fujita (1988) showed that this finding was not purely related to the increased resection time required.…”
Section: Discussionmentioning
confidence: 93%
“…(1990), we found no increased requirement for BWO in patients taking aspirin prior to TURP. In agreement with other workers, we did not demonstrate any similar relationship with any non-steroidal anti-inflammatory agent (Bricker et af., 1989) or with heparin (Wilson et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven patients had stays of less than 5 days. The mean postoperative stay was 3.9 days (range 1-11 days), 11 patients had postoperative stays of less than 3 days. A total of seven patients had a successful trial of voiding at 48 h while one patient voided at 72 h and four patients had a successful voiding trial at 120 h. Eight patients failed a trial of voiding and six of these eight patients ultimately voided at 2-4 weeks following laser prostatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…There is ample evidence that these agents are effective in reducing the incidence of deep venous thrombosis in patients having anything other than minor surgery 9 , but they may add to the risk of haemorrhagic complications 9,10 . Reports on the effect of prophylactic heparin on blood loss following transurethral prostatectomy have been contradictory, with one claiming an increase 11 and another no difference 12 .…”
Section: Discussionmentioning
confidence: 99%